SOSIALISASI DAN EDUKASI K3 DALAM UPAYA MENCEGAH RISIKO KECELAKAAN KERJA PADA UMKM DESA SASAHAN WARINGIN KURUNG SERANG BANTEN - Gede Darma Jata, Anak Agung; Ghoni, Ahmad (Gapenas Publisher, 2025)
This Community Service Program (PKM) was carried out in Sasahan Village, Waringin Kurung District, Serang Regency, with the aim of improving the understanding and skills of MSME actors regarding the implementation of Occupational Safety and Health (OSH). The low level of awareness and limited knowledge of MSMEs about the importance of OSH has led to a high potential for workplace accidents, especially in culinary, craft, and trade sectors that use simple equipment and operate in limited work environments. Through outreach and educational activities conducted on October 8–9, 2025, participants were provided with materials on basic OSH concepts, hazard identification, accident prevention strategies, as well as training on the use of personal protective equipment (PPE) and first aid for minor workplace incidents. The methods used in this program included material presentations, interactive discussions, simulations, and hands-on practice to ensure that participants could understand and apply OSH measures in simple yet effective ways. A total of 50 MSME participants took part enthusiastically, demonstrating increased awareness of the importance of creating a safe, healthy, and productive work environment. The results showed that participants began to understand that implementing OSH is not merely an obligation, but a long-term investment for business sustainability, improved productivity, and strengthened professional image of MSME. Overall, this PKM activity produced positive impacts, including increased knowledge, practical skills, and the development of collective awareness in fostering a work culture that prioritizes safety. This program is expected to serve as an initial step toward expanding OSH awareness among MSMEs and becoming a model for OSH education programs in other regions.